A high-safety niobium-titanium oxide soft-pack battery cell and its preparation method
By using niobium titanium oxide as the negative electrode material in electric vehicles and rail transit batteries, the electrode formula and electrolyte system are optimized, and the existing ternary lithium battery cells have been solved, and a high safety and high energy density battery cells have been achieved.
Patent Information
- Application Number
- CN202411937736.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The existing commercial ternary lithium liquid battery cells have poor safety performance and are difficult to pass the needle puncture test. The graphite negative electrode structure is prone to collapse, lithium dendrites are prone to occur, and the mass energy density is low.
Using niobium titanium oxide as the negative electrode material, the main material of positive and negative electrode, the electrode formula and the electrolyte system, a complete conductive network is built to improve the thermal safety performance and low-temperature working ability of the battery cell.
The high safety performance of the battery cell being pierced through an 8mm steel needle is achieved, the internal impedance of the battery cell is reduced, the normal operation is possible at -40℃, and the mass energy density is improved to 140Wh/Kg or above.
Smart Images

Figure CN119786746A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a high-safety niobium-titanium oxide soft-pack battery cell and a preparation method thereof. Background Art
[0002] Batteries for electric vehicles and rail transit, whether used for auxiliary power systems or main power systems, must pass strict safety tests to ensure reliable and efficient operation. Existing commercial ternary lithium batteries have high energy density, but the thermal stability of the materials is poor, making it difficult to pass the needle puncture test, and low-temperature charging is prone to produce lithium dendrites, posing a safety risk. Commercial lithium titanate batteries have the characteristics of fast charging and long life, but the mass energy density is very low.
[0003] The existing technical solutions have the following technical problems: The commercial ternary lithium liquid battery has poor safety performance and is difficult to pass the needle puncture test; Graphite negative electrode, lithium ions and graphite reverse intercalation reaction, lithium ions are constantly embedded and extracted, the electrode is constantly expanding and contracting, the structure is prone to collapse, leading to battery failure; The graphite negative electrode has a low potential for lithium (about 0.1V), and lithium deposition and growth of lithium dendrites easily occur. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a high-safety niobium-titanium oxide soft-pack battery cell and a preparation method thereof.
[0005] The present invention is implemented by adopting the following technical scheme: a high-safety niobium titanium oxide soft-pack battery cell, comprising a battery cell positive electrode, a battery cell negative electrode and an aluminum-plastic film for packaging, wherein the battery cell positive electrode comprises a positive electrode ear and a positive electrode sheet, and the battery cell negative electrode comprises a negative electrode ear and a negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet are arranged as a stacked assembly, and a diaphragm is also arranged between the positive electrode sheet and the negative electrode sheet for separation.
[0006] Specifically, the positive electrode ear and the negative electrode ear are both connected to the electrolyte, and the electrolyte is arranged inside the aluminum-plastic film.
[0007] Specifically, the slurry of the positive electrode of the battery cell includes lithium nickel cobalt manganese oxide, CNT, SP and poly PVDF, and the material mass ratio is: (96.2-x):2:x:1.8; wherein the value range of x is 0.5-1.
[0008] Specifically, the slurry of the negative electrode of the battery cell includes niobium titanium oxide, CNT, graphene, SP, CMC, PAA and amino alcohol dispersant, and the material mass ratio is: (94.7-x): 0.1: 1: x: 1.2: 3; wherein x ranges from 0.5 to 1; the added amount of the amino alcohol dispersant is 0.2% to 0.3% of the mass of niobium titanium oxide.
[0009] Specifically, the electrolyte includes a lithium salt, a solvent and a functional additive, and the lithium salt is a mixture of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0010] Specifically, the solvent includes at least one of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the functional additive includes at least one of fluoroethylene carbonate, propylene sulfonate, vinylene carbonate and trimethyl phosphate.
[0011] A method for preparing a high-safety niobium-titanium oxide soft-pack battery cell, used for preparing the high-safety niobium-titanium oxide soft-pack battery cell, comprises the following steps: S1: preparing positive electrode slurry, stirring and bonding lithium nickel cobalt manganese oxide, SP, CNT, PVDF and NMP, uniformly dispersing, sieving and removing iron, to obtain positive electrode slurry; S2: preparing negative electrode slurry, mixing niobium titanium oxide, CNT, graphene, SP, CMC, PAA and water to bond, adding amino alcohol dispersant to disperse evenly, sieving and removing iron, to obtain negative electrode slurry; S3: coating of positive electrode slurry, the surface density of positive electrode slurry is 122~132g / m², and the positive electrode coil is baked after coating. The baking temperature of positive electrode slurry is less than 100℃, and the wind frequency is less than 25Hz; S4: negative electrode slurry coating, the negative electrode slurry surface density is 89~109g / m², and the negative electrode coil is baked after coating. The negative electrode slurry baking temperature is less than 80℃, and the wind frequency is less than 20Hz; S5: positive electrode sheeting, rolling the positive electrode coil, the pole coil adopts a one-time rolling method, the solid density is 3.2~3.5g / m³, the rolled pole piece is laser cut to obtain the positive electrode sheet, the positive electrode sheet burr is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S6: negative electrode sheeting, rolling the negative coil material, the pole coil adopts a one-time rolling method, the solid density is 2.2~2.5g / m³, the rolled pole piece is laser die-cut to obtain the negative electrode sheet, the burr of the negative electrode sheet is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S7: stacking and assembly, stacking the die-cut positive and negative electrode sheets, rolling them into cores in the manner of wrapping the positive electrode sheets with the negative electrode sheets, with the negative electrode sheets covering the positive electrode sheets with a margin of >0.5mm, welding, short circuit testing, aluminum-plastic film wrapping and heat sealing the stacked cores to obtain semi-finished battery cells; S8: Drying and liquid injection, drying the semi-finished battery cell, after drying, the moisture content of the positive electrode is less than 200ppm, the moisture content of the negative electrode is less than 300ppm, and the moisture content of the diaphragm is less than 200ppm; lithium salt, solvent and additives are mixed in proportion, injected into the dry battery cell, and then vacuum packaged again, the liquid injection volume per ampere hour is greater than 4g, and the battery cell is left to stand at high temperature after liquid injection; S9: Formation and aging: the battery cell after injection is heated and pressurized for formation, the formation temperature is 70℃, the formation pressure is 6.5kg / cm², the formation standard is: 0.1C constant current charge and discharge for 2 weeks, the upper limit voltage of charge is 3.2V, and the lower limit voltage of discharge is 1.5V. The battery cell after formation is aged at high temperature, the temperature is 60℃, and the time is 48h; S10: Secondary sealing and capacity division, vacuum secondary sealing is performed on the aged battery cells, the vacuum degree is greater than -80kpa, the vacuum time is greater than 5s, 0.5C capacity division is performed on the secondary sealed battery cells, the capacity is selected, and the finished battery cells are obtained.
[0012] Specifically, the positive electrode slurry has a solid content of 65%, a viscosity of 7500-10000 mpa.s, and a fineness of less than 15 μm.
[0013] Specifically, the positive electrode slurry has a solid content of 40%, a viscosity of 4500-8000 mpa.s, and a fineness of <25 μm.
[0014] The beneficial effects of the present invention are as follows: the present invention optimizes the main materials of the positive and negative electrodes, the electrode formula and the electrolyte system, stabilizes the material structure, inhibits oxygen evolution, and greatly improves the thermal safety performance of the battery cell, so that the battery cell can be punctured by an 8mm steel needle. In addition, the present invention uses SP, graphene and CNT conductive agents to construct a complete conductive network, greatly reducing the internal impedance of the battery cell, so that the battery cell can work normally at -40°C. The battery cell system not only has high safety characteristics, but also has low temperature resistance. The present invention is conceived to take the advantages of lithium titanate batteries and make up for the shortcomings of ternary lithium batteries, which not only improves the safety performance of the battery cell, but also improves the mass energy density of the battery cell. Niobium titanium oxide is used as the negative electrode, and the main materials, electrode formulas and electrolytes are comprehensively optimized to meet the application requirements of batteries for electric vehicles and rail transit. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0016] Figure 1 This is a structural diagram of a high-safety niobium-titanium oxide soft-pack battery cell in an embodiment of the present invention; Figure 2 This is a flow chart for preparing a high-safety niobium-titanium oxide soft-pack battery cell in one embodiment of the present invention; Among them, 1-positive electrode ear, 2-negative electrode ear, 3-aluminum-plastic film, 4-diaphragm, 5-electrolyte, 6-niobium titanium oxide, 7-lithium nickel cobalt manganese oxide. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0018] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0019] The following is combined with Figure 1-2 , some embodiments of the present invention are described in detail. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0020] The present invention provides a high-safety niobium titanium oxide soft-pack battery cell and a corresponding preparation method thereof. In a first aspect, a high-safety niobium titanium oxide soft-pack battery cell is provided. Figure 1 As shown, it includes a positive electrode of a battery cell, a negative electrode of a battery cell and an aluminum-plastic film 3 for packaging. The positive electrode of the battery cell includes a positive electrode ear 1 and a positive electrode sheet, and the negative electrode of the battery cell includes a negative electrode ear 2 and a negative electrode sheet. The positive electrode sheet and the negative electrode sheet are arranged as a stacked assembly, and a diaphragm 4 is also arranged between the positive electrode sheet and the negative electrode sheet for separation.
[0021] In this embodiment, the positive electrode ear 1 and the negative electrode ear 2 are both connected to the electrolyte 5, and the electrolyte 5 is arranged inside the aluminum-plastic film 3. The slurry of the positive electrode of the battery cell includes lithium nickel cobalt manganese oxide, CNT, SP and poly PVDF, and the material mass ratio is: (96.2-x):2:x:1.8; wherein x ranges from 0.5 to 1.
[0022] In this embodiment, the slurry of the negative electrode of the battery cell includes niobium titanium oxide, CNT, graphene, SP, CMC, PAA and amino alcohol dispersant, and the material mass ratio is: (94.7-x): 0.1: 1: x: 1.2: 3; wherein x ranges from 0.5 to 1; and the added amount of the amino alcohol dispersant is 0.2% to 0.3% of the mass of the niobium titanium oxide.
[0023] In this embodiment, the electrolyte 5 includes a lithium salt, a solvent and a functional additive, and the lithium salt is a mixture of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0024] In this embodiment, the solvent includes at least one of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the functional additive includes at least one of fluoroethylene carbonate, propylene sulfonate, vinylene carbonate and trimethyl phosphate.
[0025] The present invention also correspondingly proposes a method for preparing a high-safety niobium-titanium oxide soft-pack battery cell, which is used to prepare the high-safety niobium-titanium oxide soft-pack battery cell, comprising the following steps: S1: preparing positive electrode slurry, stirring and bonding lithium nickel cobalt manganese oxide, SP, CNT, PVDF and NMP, uniformly dispersing, sieving and removing iron, to obtain positive electrode slurry; S2: preparing negative electrode slurry, mixing niobium titanium oxide, CNT, graphene, SP, CMC, PAA and water to bond, adding amino alcohol dispersant to disperse evenly, sieving and removing iron, to obtain negative electrode slurry; S3: coating of positive electrode slurry, the surface density of positive electrode slurry is 122~132g / m², and the positive electrode coil is baked after coating. The baking temperature of positive electrode slurry is less than 100℃, and the wind frequency is less than 25Hz; S4: negative electrode slurry coating, the negative electrode slurry surface density is 89~109g / m², and the negative electrode coil is baked after coating. The negative electrode slurry baking temperature is less than 80℃, and the wind frequency is less than 20Hz; S5: positive electrode sheeting, rolling the positive electrode coil, the pole coil adopts a one-time rolling method, the solid density is 3.2~3.5g / m³, the rolled pole piece is laser cut to obtain the positive electrode sheet, the positive electrode sheet burr is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S6: negative electrode sheeting, rolling the negative coil material, the pole coil adopts a one-time rolling method, the solid density is 2.2~2.5g / m³, the rolled pole piece is laser die-cut to obtain the negative electrode sheet, the burr of the negative electrode sheet is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S7: stacking and assembly, stacking the die-cut positive and negative electrode sheets, rolling them into cores in the manner of wrapping the positive electrode sheets with the negative electrode sheets, with the negative electrode sheets covering the positive electrode sheets with a margin of >0.5mm, welding, short circuit testing, aluminum-plastic film wrapping and heat sealing the stacked cores to obtain semi-finished battery cells; S8: Drying and liquid injection, drying the semi-finished battery cell, after drying, the moisture content of the positive electrode is less than 200ppm, the moisture content of the negative electrode is less than 300ppm, and the moisture content of the diaphragm is less than 200ppm; lithium salt, solvent and additives are mixed in proportion, injected into the dry battery cell, and then vacuum packaged again, the liquid injection volume per ampere hour is greater than 4g, and the battery cell is left to stand at high temperature after liquid injection; S9: Formation and aging: the battery cell after injection is heated and pressurized for formation, the formation temperature is 70℃, the formation pressure is 6.5kg / cm², the formation standard is: 0.1C constant current charge and discharge for 2 weeks, the upper limit voltage of charge is 3.2V, and the lower limit voltage of discharge is 1.5V. The battery cell after formation is aged at high temperature, the temperature is 60℃, and the time is 48h; S10: Secondary sealing and capacity division, vacuum secondary sealing is performed on the aged battery cells, the vacuum degree is greater than -80kpa, the vacuum time is greater than 5s, 0.5C capacity division is performed on the secondary sealed battery cells, the capacity is selected, and the finished battery cells are obtained.
[0026] In this embodiment, the positive electrode slurry has a solid content of 65%, a viscosity of 7500-10000 mPa.s, and a fineness of less than 15 μm.
[0027] In this embodiment, the positive electrode slurry has a solid content of 40%, a viscosity of 4500-8000 mpa.s, and a fineness of <25 μm. In another embodiment, a high-safety niobium titanium oxide soft-pack battery cell and a method for preparing the same, such as Figure 2 As shown, the following steps are included: S1: preparing positive electrode slurry, stirring and bonding lithium nickel cobalt manganese oxide, SP, CNT, PVDF and NMP, uniformly dispersing, passing through a 120-mesh sieve, removing iron, and obtaining positive electrode slurry; S2: preparing negative electrode slurry, stirring and bonding niobium titanium oxide, CNT, graphene, SP, CMC, PAA and water, adding amino alcohol dispersant to disperse uniformly, passing through a 150 mesh sieve, removing iron, and obtaining negative electrode slurry; S3: coating of positive electrode slurry, the surface density of positive electrode slurry is 122~132g / m², and the positive electrode coil is baked after coating. The baking temperature of positive electrode slurry is less than 100℃, and the wind frequency is less than 25Hz; S4: negative electrode slurry coating, the negative electrode slurry surface density is 89~109g / m², and the negative electrode coil is baked after coating. The negative electrode slurry baking temperature is less than 80℃, and the wind frequency is less than 20Hz; S5: positive electrode sheeting, rolling the positive electrode coil, the pole coil adopts a one-time rolling method, the solid density is 3.2~3.5g / m³, the rolled pole piece is laser cut to obtain the positive electrode sheet, the positive electrode sheet burr is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S6: negative electrode sheeting, rolling the negative coil material, the pole coil adopts a one-time rolling method, the solid density is 2.2~2.5g / m³, the rolled pole piece is laser die-cut to obtain the negative electrode sheet, the burr of the negative electrode sheet is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S7: stacking-assembly, stacking the die-cut positive and negative electrode sheets, rolling them into cores by wrapping the positive electrode sheets with the negative electrode sheets, with the negative electrode sheets covering the positive electrode sheets with a margin of >0.5mm, welding the stacked cores, testing short circuits, wrapping with aluminum-plastic film, and heat-sealing to obtain semi-finished battery cells; S8: Drying-liquid injection, drying the semi-finished battery cell, drying temperature 90℃, drying time 36h, after drying, the moisture content of positive electrode is less than 200ppm, the moisture content of negative electrode is less than 300ppm, and the moisture content of diaphragm is less than 200ppm. Lithium salt, solvent and additives are mixed in proportion, injected into the dry battery cell, and then vacuum packaged again, the liquid injection volume per ampere hour is greater than 4g, after liquid injection, the battery cell is left to stand at high temperature, temperature 60℃, time 48h; S9: Formation-Aging: The battery cell after injection is heated and pressurized for formation, the formation temperature is 70℃, the formation pressure is 6.5kg / cm², the formation standard is: 0.1C constant current charge and discharge for 2 weeks, the upper limit voltage of charge is 3.2V, and the lower limit voltage of discharge is 1.5V. The battery cell after formation is aged at high temperature, the temperature is 60℃, and the time is 48h; S10: Secondary sealing - capacity separation, vacuum secondary sealing is performed on the aged battery cells, the vacuum degree is greater than -80kpa, the vacuum time is greater than 5s, 0.5C capacity separation is performed on the secondary sealed battery cells, the capacity is selected, and the finished battery cells are obtained.
[0028] Compared with the prior art, the present invention has the following main advantages: 1. The existing commercial ternary lithium liquid battery has poor safety performance and is difficult to pass the needle puncture test. The present invention uses a ternary positive electrode with a niobium titanium oxide negative electrode, which can be punctured by an 8mm steel needle, and the battery cell will not catch fire or explode.
[0029] 2. In the existing graphite negative electrode, lithium ions react with graphite to form an intercalation layer, lithium ions are constantly embedded and extracted, the electrode is constantly expanding and contracting, the structure is easily collapsed, and the battery cell fails. The negative electrode of the present invention uses niobium titanium oxide. The embedding and extraction of lithium ions during the charge and discharge process has almost no effect on the crystal structure of the material, and almost no structural damage occurs during the charge and discharge cycle.
[0030] 3. The existing graphite negative electrode has a low potential for lithium (about 0.1V), which is prone to lithium deposition and growth of lithium dendrites. The negative electrode of the present invention uses niobium titanium oxide, which has a high potential for lithium (about 1.5V) and is not easy to form SEI film, which can effectively inhibit the generation of metal lithium dendrites and greatly reduce the risk of internal runaway of the battery cell.
[0031] 4. The mass energy density of existing lithium titanate batteries is generally low (about 90Wh / Kg). The present invention uses niobium titanium oxide as the negative electrode, and the mass energy density of the battery is increased by more than 50% compared with the existing technology to reach 140Wh / Kg.
[0032] For the aforementioned embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should be aware that the present application is not limited by the order of the actions described, because according to the present application, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also be aware that the embodiments described in the specification are preferred embodiments, and the actions involved are not necessarily required by the present application.
[0033] The above embodiments describe the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the changes and modifications made by those skilled in the art shall be within the scope of protection of the appended claims of the present invention without departing from the spirit and scope of the present invention.
Claims
1. A high-safety niobium titanium oxide soft-pack battery cell, characterized in that: The battery cell comprises a positive electrode, a negative electrode and an aluminum-plastic film (3) for packaging. The positive electrode comprises a positive electrode ear (1) and a positive electrode sheet. The negative electrode comprises a negative electrode ear (2) and a negative electrode sheet. The positive electrode sheet and the negative electrode sheet are arranged as a stacked assembly. A diaphragm (4) is also arranged between the positive electrode sheet and the negative electrode sheet for separation.
2. A high-safety niobium-titanium oxide soft-pack battery cell as claimed in claim 1, characterized in that: The positive electrode ear (1) and the negative electrode ear (2) are both connected to an electrolyte (5), and the electrolyte (5) is arranged inside the aluminum-plastic film (3).
3. The high-safety niobium-titanium oxide soft-pack battery cell according to claim 1, characterized in that: The slurry of the positive electrode of the battery cell includes lithium nickel cobalt manganese oxide, CNT, SP and poly PVDF, and the material mass ratio is: (96.2-x):2:x:1.8; wherein the value range of x is 0.5-1.
4. The high-safety niobium-titanium oxide soft-pack battery cell according to claim 1, characterized in that: The slurry of the negative electrode of the battery cell includes niobium titanium oxide, CNT, graphene, SP, CMC, PAA and amino alcohol dispersant, and the material mass ratio is: (94.7-x): 0.1: 1: x: 1.2: 3; wherein the value range of x is 0.5 to 1; the added amount of the amino alcohol dispersant is 0.2% to 0.3% of the mass of the niobium titanium oxide.
5. The high-safety niobium-titanium oxide soft-pack battery cell according to claim 1, characterized in that: The electrolyte (5) comprises a lithium salt, a solvent and a functional additive, wherein the lithium salt is a mixture of lithium bis(fluorosulfonate)imide and lithium hexafluorophosphate.
6. A high-safety niobium-titanium oxide soft-pack battery cell as claimed in claim 5, characterized in that: The solvent includes at least one of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the functional additive includes at least one of fluoroethylene carbonate, propylene sulfonate, vinylene carbonate and trimethyl phosphate.
7. A method for preparing a high-safety niobium-titanium oxide soft-pack battery cell, used to prepare a high-safety niobium-titanium oxide soft-pack battery cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: preparing positive electrode slurry, stirring and bonding lithium nickel cobalt manganese oxide, SP, CNT, PVDF and NMP, uniformly dispersing, sieving and removing iron, to obtain positive electrode slurry; S2: preparing negative electrode slurry, mixing niobium titanium oxide, CNT, graphene, SP, CMC, PAA and water to bond, adding amino alcohol dispersant to disperse evenly, sieving and removing iron, to obtain negative electrode slurry; S3: coating of positive electrode slurry, the surface density of positive electrode slurry is 122~132g / m², and the positive electrode coil is baked after coating. The baking temperature of positive electrode slurry is less than 100℃, and the wind frequency is less than 25Hz; S4: negative electrode slurry coating, the negative electrode slurry surface density is 89~109g / m², and the negative electrode coil is baked after coating. The negative electrode slurry baking temperature is less than 80℃, and the wind frequency is less than 20Hz; S5: positive electrode sheeting, rolling the positive electrode coil, the pole coil adopts a one-time rolling method, the solid density is 3.2~3.5g / m³, the rolled pole piece is laser cut to obtain the positive electrode sheet, the positive electrode sheet burr is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S6: negative electrode sheeting, rolling the negative coil material, the pole coil adopts a one-time rolling method, the solid density is 2.2~2.5g / m³, the rolled pole piece is laser die-cut to obtain the negative electrode sheet, the burr of the negative electrode sheet is less than 12μm, and there is no molten bead stacking on the edge of the pole piece; S7: stacking and assembly, stacking the die-cut positive and negative electrode sheets, rolling them into cores in the manner of wrapping the positive electrode sheets with the negative electrode sheets, with the negative electrode sheets covering the positive electrode sheets with a margin of >0.5mm, welding, short circuit testing, aluminum-plastic film wrapping and heat sealing the stacked cores to obtain semi-finished battery cells; S8: Drying and liquid injection, drying the semi-finished battery cell, after drying, the moisture content of the positive electrode is less than 200ppm, the moisture content of the negative electrode is less than 300ppm, and the moisture content of the diaphragm is less than 200ppm; lithium salt, solvent and additives are mixed in proportion, injected into the dry battery cell, and then vacuum packaged again, the liquid injection volume per ampere hour is greater than 4g, and the battery cell is left to stand at high temperature after liquid injection; S9: Formation and aging: the battery cell after injection is heated and pressurized for formation, the formation temperature is 70℃, the formation pressure is 6.5kg / cm², the formation standard is: 0.1C constant current charge and discharge for 2 weeks, the upper limit voltage of charge is 3.2V, and the lower limit voltage of discharge is 1.5V; the battery cell after formation is aged at high temperature, the temperature is 60℃, and the time is 48h; S10: Secondary sealing and capacity division, vacuum secondary sealing is performed on the aged battery cells, the vacuum degree is greater than -80kpa, the vacuum time is greater than 5s, 0.5C capacity division is performed on the secondary sealed battery cells, the capacity is selected, and the finished battery cells are obtained.
8. A method for preparing a high-safety niobium-titanium oxide soft-pack battery cell according to claim 7, characterized in that: The positive electrode slurry has a solid content of 65%, a viscosity of 7500-10000 mpa.s, and a fineness of less than 15 μm.
9. A method for preparing a high-safety niobium-titanium oxide soft-pack battery cell according to claim 8, characterized in that: The positive electrode slurry has a solid content of 40%, a viscosity of 4500-8000 mpa.s, and a fineness of less than 25 μm.